Evidence of a strong perpendicular magnetic anisotropy in Au/Co/MgO/GaN heterostructures. Issue 11 (21st October 2019) - Gao, Xue; Yang, Baishun; Devaux, Xavier; Yang, Hongxin; Liu, Jianping; Liang, Shiheng; Stoffel, Mathieu; Pasquier, Ludovic; Hyot, Bérangère; Grenier, Adeline; Bernier, Nicolas; Migot, Sylvie; et al.
Abstract : We demonstrate that a 4.6 nm thick Co film grown on MgO/GaN still exhibits a large perpendicular magnetic anisotropy. Abstract : We report a strong perpendicular magnetic anisotropy (PMA) in Au/Co/MgO/GaN heterostructures from both experiments and first-principles calculations. The Au/Co/MgO heterostructures have been grown by molecular beam epitaxy (MBE) on GaN/sapphire substrates. By carefully optimizing the growth conditions, we obtained a fully epitaxial structure with a crystalline orientation relationship Au(111)[1̄10]//Co(0001)[112̄0]//MgO(111)[101̄]//GaN(0002)[112̄0]. More interestingly, we demonstrate that a 4.6 nm thick Co film grown on MgO/GaN still exhibits a large perpendicular magnetic anisotropy. First-principles calculations performed on the Co (4ML)/MgO(111) structure showed that the MgO(111) surface can strongly enhance the magnetic anisotropy energy by 40% compared to a reference 4ML thick Co hcp film. Our layer-resolved and orbital-hybridization resolved anisotropy analyses helped to clarify that the origin of the PMA enhancement is due to the interfacial hybridization of O 2p and Co 3d orbitals at the Co/MgO interface. The perpendicularly magnetized Au/Co/MgO/GaN heterostructures are promising for efficient spin injection and detection in GaN based opto-electronics without any external magnetic field.